Problem nisko opłacanych pracowników w Polsce na tle innych krajów gospodarki rynkowej - Golnau, Wiesław (Annales. Etyka w Życiu Gospodarczym, 2008)
Research which has been carried out in countries with developed market economies indicates that since the 1980s there has been a systematic increase in wage inequality. As a result, low-wage employment has increased. In recent years, many academic institutions in developed countries have been conducting research into the scale, causes and consequences of low wages. Such research has not as yet been systematically carried out in Poland. This article aims to contribute to the research. Its objective is to establish the scale and causes of low-wage employment in Poland in the last sixteen years. The contents of the article are divided into three parts. The first part is devoted to the methodology of measuring low wages. The second part concerns the frequency of low wages in Poland and other countries with market economies. The third part of the article presents factors influencing the scale of the occurrence of low wages. According to the research, the number of people in low-wage employment in Poland systematically increased in the period from 1989 to 2004. In 2004 this number exceeded 22% of all working people. A similarly high percentage of low-wage employment is found only in Korea, Hungary, Great Britain, the USA and Canada.